PERANCANGAN SISTEM AUTENTIKASI MULTI-ROLE BERBASIS RBAC PADA PLATFORM E-LEARNING PEMBERDAYAAN EKONOMI PEREMPUAN - Rizal Firmansyah; Aulia Hamdi; Dini Riandini (LPPM Universitas Abdurrab, 2026)
Digital transformation provides significant opportunities for women’s economic empowerment. The UMI (Usaha Mandiri Ibu) platform was developed as a web-based Learning Management System (LMS) to bridge the gap for housewives by monetizing their domestic skills. However, the presence of multiple user roles (Participants, Mentors, and Super Admins) creates a complex interaction ecosystem. This diversity of roles introduces potential security risks, especially related to unauthorized access or privilege escalation if not managed with a proper access-control mechanism. This study aims to design and implement a multi-role authentication system on the UMI platform using the Role-Based Access Control (RBAC) method. The system development process adopts the Waterfall model, consisting of requirement analysis, system design, implementation using ReactJS and ExpressJS, and testing. Specifically, the built system integrates the RBAC mechanism at the middleware layer to verify user authority in real-time, ensuring strict access separation between administrative and learning features. The testing results demonstrate that the authentication process and role-based authorization restrictions function correctly with a 100% success rate. These findings indicate that the RBAC model is effective in enforcing strict separation of access privileges, enhancing data security and system integrity for the UMI platform.